Directional preparation of indigo or indirubin from indican by an alkali-resistant glucosidase under specific pH and temperature. (February 2023) - Luo, Jianianhua; Zhang, Xiaomeng; Wang, Xinyi; Pei, Jianjun; Zhao, Linguo
Abstract: Indigo has a unique value in industrial applications, and its isomer, indirubin, is pharmacologically active against multiple diseases. However, specific transformation processes of indican to its final products (indigo or indirubin) are inefficient, which hampers the isolation of high-purity products. We characterized an enzyme of the GH1-family and regulated its catalytic processes to achieve specific transformation. The target alkali-stable glucosidase gene was overexpressed in Escherichia coli BL21 (DE3). Under optimized induction conditions, alkali-stable glucosidase with an activity of 24.221 U/mL was produced. Asbg1 exhibited significant activities in a wide range of pH conditions, with optimum activities being established at pH 8.5. Indican was rapidly hydrolyzed into desired final products by adjusting the temperature and pH ranges of the enzymatic reaction. The final maximum productivity of single indigo and indirubin were obtained at pH 7.5 and 55 ℃ and pH 9.5 and 45 ℃, respectively. The titer of indigo was further increased to 97.881% by conducting the reaction in a water bath with agitation at a speed of 250 rpm. The addition of cysteine inhibited indigo production but improved the proportion of produced indirubin to 88.381%. Graphical Abstract: ga1 Highlights: A simple method of adjusting the temperature and pH via the reaction for directional preparation of high purity indigo or indirubin. A new glucosidase was studied, which could enrich the resources of glucosidase. Improving the productivity of Asbg1.